(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Huda MK, Pasaribu N, Syamsuardi, Siregar ES. 2022. Diversity, risk and management feasibility of invasive alien plants in the border zone of Sicike-cike Nature Tourism Park, North Sumatra, Indonesia. Biodiversitas 23: 3156-3165. Invasive alien species (IAS) threaten native ecosystems and biota either directly or indirectly. Once colonizing, invasive plant species tend to dominate a landscape, hindering other native vegetation from growing. Thus, the invasion of alien plant species needs attention moreover in protected areas such as Nature Tourism Park (Taman Wisata Alam/TWA) Sicike-cike, Dairi District, North Sumatra, Indonesia. Besides its importance for nature conservation, TWA Sicike-cike is culturally essential for Pakpak Dairi ethnic community as well as economically for ecotourism. Yet, anecdotal evidence showed the presence of several invasive alien plants around the park. This study aimed to investigate the diversity and composition of invasive alien plants within the vegetation community in TWA Sicike-cike and to assess the risk value and management feasibility of the IAS. Purposive sampling using line transect method was conducted to collect data with a total of 120 observation plots established along 6 transects. Risk value was assessed based on invasiveness, impact and potential distribution. Management feasibility was assessed based on cost, current distribution and persistence. The results showed that Asteraceae was the most dominant family of invasive plants in the studied area with four species. At the species level, Imperata cylindrica was invasive alien plant species with the highest important value index (IVI) of 57.65% and a high-risk value of 235.8, followed by other species including Ageratum conyzoides, Chromolaena odorata, Clidemia hirta and Melastoma malabathricum. In terms of management feasibility, the existence of I. cylindrica is recommended for direct eradication, while other IAS management recommendations, included monitoring and area protection for further invasion by the species.